Study of the relationship between fruit mineral concentration and bitter pit in apples, with special reference to 'Braeburn' - Le Grange, Sarah A (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1995.